Isoflurane sedation in patients undergoing VA-ECMO treatment for cardiogenic shock. (26th April 2021) - Scherer, C; Kupka, D; Luesebrink, E; Massberg, S; Orban, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Objectives (Background): The feasibility and hemodynamic effects of isoflurane sedation in cardiogenic shock in the presence of extracorporeal membrane oxygenation (VA-ECMO) treatment is currently unknown. Design: Retrospective single-center study Patients/subjects: Cardiogenic shock patients with VA-ECMO treatment under sedation with volatile isoflurane between November 2018 and October 2019 have been enrolled in this study and were matched by propensity score in a 1:1 ratio with intravenously (IV) sedated patients treated between January 2013 and November 2018 from the cardiogenic shock registry of our university hospital. Measurements and Main Results: Isoflurane sedation was used in 32 patients with cardiogenic shock and VA-ECMO treatment. The mean age of conventionally sedated patients was 58.4 ± 13.8 years and 56.3 ± 11.5 years for patients with isoflurane sedation (p = 0.51). Administration of isoflurane was associated with lower IV sedative drug use during VA-ECMO treatment (86% vs. 32%, p = 0.01). Mean systolic arterial pressure was similar (94.3 ± 12.6 mmHg versus 92.9 ± 10.5 mmHg, p = 0.65), but mean heart rate was significantly higher in the conventional sedation group, when compared to the isoflurane group (85.2 ± 20.5 /min vs. 74.7 ± 15.0 /min; p = 0.02). Catecholamine doses, VA-ECMO blood and gas flow, ventilation time (304 ± 143 h vs. 398 ± 272 h, p = 0.16), bleeding complications BARC3a or higher (59.3% vs. 65.3%, p = 0.76) and 30 day-mortality (59.2% vs. 63.4%, p = 0.80) were similar in both groups. The overall sedation costs per patient were significantly lower in the conventional group, when compared to the isoflurane group (537 ± 624 € vs. 1280 ± 837 €, p < 0.001). Conclusions: Volatile sedation with isoflurane is feasible – albeit at higher costs - in patients with cardiogenic shock and VA-ECMO treatment and was not associated with higher catecholamine dosage or ECMO flow rate compared to IV sedation.